Tingkat Nyeri Desminore pada Remaja dengan Massage Efflurage di SMAN 1 Cihaurbeuti - Mukti, Arifah Septiane; Hindiarti, Yudita Ingga; Heryani, Sri (Journal of Midwifery and Public Health, 2024)
Efflurage massage is a method of massaging using the palms of the hands to apply gentle pressure to the surface of the body in a repeated direction of circulation. This technique aims to increase blood circulation, apply pressure and warm the abdominal muscles and increase physical and mental relaxation. Dysmenorrhea is pain or cramps that women feel in the lower abdomen area which occurs before or after experiencing the first day of menstruation (menarche) until the second day. The aim of this study was to determine the effect of massage efflurage on reducing desminorrhea pain. The method in this research is Quasi-Experimental research using the One Group Pretest-Posttest Design research method. The results of this study were that those who experienced desminore pain levels before efflurage massage were 14 respondents (47%) with severe desminore pain levels, 9 people (30%) with moderate pain levels and 18 (60%) respondents after efflurage massage. mild pain level. The conclusion from this study is that there is an effect of efflurage massage on reducing the level of desminore pain. Advice for teenagers is that when experiencing desminorrhea, they should try not to consume drugs and herbal medicines, and should do efflurage massage.